Paciente de 31 semanas de embarazo con polihidramnios. - Copete Litardo, Genesis Jisleny (2023)
Amniotic fluid is the fluid that surrounds the fetus within the ovular membranes in the uterine cavity during its development. In case of an increase it is called polyhydramnios and in an excessive decrease it is called oligohydramnios. Polyhydramnios is the excessive accumulation of amniotic fluid, its presence implies maternal and fetal complications in 50% to 60% idiopathic. We found 3 levels of severity for the diagnosis: Mild ALF 18-25 Moderate ALF: 25-32 Severe ALF: >32 This is associated with fetal-maternal complications; the diagnosis can be observed by ultrasound. The case of a 25-year-old of polyhydramnios with a 31-week pregnancy with clinical symptoms due to uterine activity and loss of amniotic fluid is presented.